Werklozenkamp. Derde van rechts: minister Romme. Kopie van een foto uit het Fotoarchief Spaarnestad, neg.nr. 2001/16
Werklozenkamp. Derde van rechts: minister Romme. Kopie van een foto uit het Fotoarchief Spaarnestad, neg.nr. 2001/16.